B602L-Fc fusion protein enhances the immunogenicity of the B602L protein of the African swine fever virus - Yang, Yang; Xia, Qiqi; Zhou, Lujia; Zhang, Yan; Guan, Zhixin; Zhang, Junjie; Li, Zongjie; Liu, Ke; Li, Beibei; Shao, Donghua; Qiu, Yafeng; Ma, Zhiyong; et al. (Frontiers in Immunology, 2023)
African swine fever (ASF) is an acute, highly contagious, and deadly infectious disease caused by the African swine fever virus (ASFV) and has a huge impact on the pig industry. A lack of vaccines and effective therapeutic drugs has brought great challenges to the prevention and control of ASF. This study aimed to express ASFV B602L protein (B602L) alone and the IgG Fc-fused B602L protein (B602L-Fc) using insect baculovirus expression system and evaluate the immune effect of B602L-Fc in mice model. To be specific, the ASFV B602L protein and B602L-Fc fusion protein were successfully expressed by the insect baculovirus expression system. Then, Functional analysis in vitro revealed that the B602L-Fc fusion protein bound and interacted with the FcRI receptor of antigen-presenting cells and significantly promoted the expression of proteins involved in antigen presentation and various cytokines at mRNA levels in porcine alveolar macrophages. Additionally, immunization using B602L-Fc fusion protein remarkably promoted the Th1-biased cellular immune response and humoral immune response in mice. The data suggest that ASFV B602L-Fc recombinant fusion protein may be a promising candidate for subunit vaccine. In conclusion, The B602L-Fc fusion protein could up-regulate the expression of molecules involved in antigen presentation in APCs and enhance the humoral and cellular immune responses in mice. This study provided useful data for the development of subunit vaccines for ASF. Keywords: African swine fever virus, B602L, IgG Fc, Subunit vaccine, Immunogenicity